Effect of Microfinance Services on Financial Performance of Selected Small and Medium Enterprises in Gisagara District, Rwanda - NYIRANSABIMANA , Evelyne; Tarus , Thomas (Journal of Finance and Accounting, 2023)
The general objective of this research was to assess the effect of microfinance services on financial performance of small and medium enterprises in Rwanda. This study had the following specific objectives; to find out effect of financial literacy on financial performance of small medium enterprises in Gisagara District, examine the effect of saving services on financial performance of small and medium enterprises in Gisagara District and determine the effect of access to credit services on financial performance of small and medium enterprises in Gisagara District. For this study 6984 Small and Medium Enterprises as members of SACCOs in Gisagara District made up the study’s population. The sample size determined by the help of Solvin’s formula. Respondents selected from the clusters using a basic random sampling method for the study. As all 378 respondents are members of SACCOs in Gisagara District, random sampling used to choose a representative sample from each division. Each study goal probed with detailed inquiries to guarantee its fruitful conclusion. The study employed descriptive and inferential statistics. The findings indicate the coefficients between financial literacy, saving services, credit services, and financial performance of the respondents. There is significant effect of financial literacy on financial performance of SMEs (β=0.335, p<0.05). There is a significant effect of saving services on financial performance of SMEs (β = 0.273, p < 0.05). This indicates that individuals who utilize saving services tend to have better financial performance in their businesses. There is a significant effect of credit services on financial performance of SMEs (β=0.337, p<0.05). These findings highlight the importance of financial literacy, access to saving and credit services in promoting better financial outcomes for entrepreneurs and small and medium enterprises in Gisagara District. To enhance the financial performance of small and medium enterprises (SMEs) in Gisagara District, it is recommended to implement targeted financial literacy programs that address the specific needs of SMEs and collaborate with local stakeholders to ensure widespread adoption of financial best practices.